Understanding Moral Empathy: A Phenomenological Exploration - Pieris, Dilshan (My University, 2019)
Background: Empathy is essential to forming strong patient-physician relationships that enable physicians to provide better healthcare. In the medical education literature, empathy consists of cognitive, affective, behavioural, and moral domains. Studies have measured declines in empathy during medical training. Researchers speculate that factors within formal, informal, and hidden curricula contribute to empathic decline. Several frameworks suggest that empathy in the moral domain (i.e., the inner motivation to accept patients unconditionally, commit to understanding patients, and help patients achieve their needs) is the most fundamental to the empathic response. Studying the factors that influence moral empathy during training is important to developing insights into the reasons for the demonstrated declines in resident empathy. Methods: Descriptive phenomenology was used to address the research objective. Medical residents from various specialties participated in lightly structured interviews concerning their experiences. Interview transcripts were inductively and collaboratively analyzed to construct a preliminary set of factors that influence moral empathy. These factors informed the creation of a script for a verbatim theatre play that was performed for an audience of residents, educators, learners, researchers, and scholars. Following the play, audience participants completed a survey that served as a member-check of the factors that contributed to the final construction of factors. Results: The results were constructed as three categories under which seven factors are nested. These categories are: Innate Capacity, Previous Personal Encounters, and Specific Patient Encounters. With the exception of a few, most factors do not directly influence residents’ moral empathy but rather challenge their ability to act on their moral empathy. Discussion: These results offer unique insights into the declines in empathy that have been previously reported in the medical education literature, while also highlighting a moral-behavioural tension that has implications for competency-based medical education, the four-factor model of empathy, and the assessment of empathy in medical education. Future work may build on the results of this study to develop an assessment tool for moral empathy and to elucidate the relationships between the domains of empathy in order to arrive at a more refined conceptualization of the construct.
Keywords: empathy; motivation; phenomenology; verbatim theatre; medical education